Abnormal iron homeostasis and neurodegeneration - Muhoberac, Barry B.; Vidal, Ruben (Frontiers in Aging Neuroscience, 2013)
Abnormal iron metabolism is observed in many neurodegenerative diseases, however, only two have shown dysregulation of brain iron homeostasis as the primary cause of neurodegeneration. Herein, we review one of these - hereditary ferritinopathy (HF) or neuroferritinopathy, which is an autosomal dominant, adult onset degenerative disease caused by mutations in the ferritin light chain (FTL) gene. HF has a clinical phenotype characterized by a progressive movement disorder, behavioral disturbances, and cognitive impairment. The main pathologic findings are cystic cavitation of the basal ganglia, the presence of ferritin inclusion bodies (IBs), and substantial iron deposition. Mutant FTL subunits have altered sequence and length but assemble into soluble 24-mers that are ultrastructurally indistinguishable from those of the wild type. Crystallography shows substantial localized disruption of the normally tiny 4-fold pores between the ferritin subunits because of unraveling of the C-termini into multiple polypeptide conformations. This structural alteration causes attenuated net iron incorporation leading to cellular iron mishandling, ferritin aggregation, and oxidative damage at physiological concentrations of iron and ascorbate. A transgenic murine model parallels several features of HF, including a progressive neurological phenotype, ferritin IB formation, and misregulation of iron metabolism. These studies provide a working hypothesis for the pathogenesis of HF by implicating (1) a loss of normal ferritin function that triggers iron accumulation and overproduction of ferritin polypeptides, and (2) a gain of toxic function through radical production, ferritin aggregation, and oxidative stress. Importantly, the finding that ferritin aggregation can be reversed by iron chelators and oxidative damage can be inhibited by radical trapping may be used for clinical investigation. This work provides new insights into the role of abnormal iron metabolism in neurodegeneration.